Filogeografia como escopo para explorar a invasão em Ludwigia (Onagraceae) de ambientes não nativos. - Silva, Adrian Cesar da (2022)
Ludwigia has some invasive macrophyte species that have not yet been explored under the scope of phylogeography, a promising area to understand the ecology of invasions using barcode molecular markers sensitive to intraspecific variations. Thus, it was theorized that barcode markers used in invasive species of Ludwigia occurring in non-native regions would be phylogeographically informative. Sequences of the molecular markers trnH-psbA, rbcL, matK and phyC from invasive populations of L. peploides and L. grandiflora were used as they are the only ones available in Genbank. A gene tree was generated by the Neighborn-Joining method and a haplotypic network by the Median-Joining method for each species. The trnH-psbA marker was the only phylogeographically informative marker for detecting intraspecific variations in the analyzed taxa. Three haplotypes were detected for L. grandiflora and two haplotypes for L. peploides. Three geographically distinct founder populations of L. grandiflora were introduced in Europe, with Hg1 shared with the US population, while L. peploides has a founder population in Europe and another in the US. The long history of the introduction of these species in Europe and the limited geographic scope of molecular sampling demonstrate that these data are underestimated. A search in the Web of Science database exposed a paucity of molecular data for invasive species of Ludwigia, highlighting the contribution of the results to the information on these haplotypic relationships in the context of invasive biology. Therefore, the detection of haplotypic diversity of invasive species of Ludwigia proved to be promising when investigated by the phylogeographic scope, supporting a better understanding of the management and ecology of these haplotypes in non-native areas.